Sodobni pristop k jezikovnemu svetovanju v gledališču na Slovenskem - Vrtačnik, Martin; Tivadar, Hotimir (Slavia Centralis, 2020)
The article brings an elaboration of contemporary approaches to language consulting in drama theatre. In the framework of the history of theatrical language consulting, the article emphasises the importance of modern dramaturgic concepts when shaping contemporary stage speech. Based on Dušan Jovanović’s staging of the text Generacije (Generations) (1977), the article demonstrates the linguistic viewpoint of the dramaturge and language consultant, Marko Slodnjak, who overcame the conservativism ingrained in stage speech at the time. Slodnjak’s linguistic viewpoint and critical responses to Generacije serve as a starting point for the formation of a new, cognitivism-based model of language consulting in the framework of stage speech.
Keywords: stage speech; normativity; cognitive linguistics; drama theatre; language consulting